2017
DOI: 10.17533/udea.iee.v35n1a03
|View full text |Cite
|
Sign up to set email alerts
|

Educational process in palliative care and the thought reform

Abstract: Artículo ligado a la investigación: Ensino educativo em cuidados paliativos e atuação do enfermeiro na terminalidade: um estudo de caso. How to cite this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 10 publications
0
24
0
11
Order By: Relevance
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme. Regarding the place of origin of the studies, it was observed that they were from several countries, with predominance of six articles from the United States of America (USA) (13,(15)(16)(17)20,25) , three from Brazil (2,7,12) , two from the United Kingdom (14,19) , two from India (11,22) , two from Canada (23)(24) , one from Argentina (21) and one from the Republic of Cyprus (18) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations